2022
DOI: 10.1021/acs.jpcc.2c07597
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Short-Range and Three-Membered Ring Structures in Lithium Borosilicate Glasses Using a Machine-Learning Potential

Abstract: Lithium borosilicate (LBS) glass is a prototypical lithium-ion conducting oxide glass available for an all-solid-state buttery. Nevertheless, the atomistic modeling of LBS glass using ab initio (AIMD) and classical molecular dynamics (CMD) simulations has critical limitations due to computational cost and inaccuracy in reproducing the glass microstructures, respectively. To overcome these difficulties, a machine-learning potential (MLP) was examined in this work for modeling LBS glasses using DeepMD. The glass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 52 publications
1
8
0
Order By: Relevance
“…The predicted atomic forces also give satisfactory results with an MAE of 0.154 eV/Å. These values are comparable with MAEs obtained in other works on MLP trained on specific glass compositions. , No particular trend was observed either with the composition changes or with different elements present in the systems, suggesting that the proposed MLP describes with comparable accuracy glasses within the full compositional range of glass formability. Albeit the virial was not included in the training, its prediction is accurate with MAE = 3.254 eV.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…The predicted atomic forces also give satisfactory results with an MAE of 0.154 eV/Å. These values are comparable with MAEs obtained in other works on MLP trained on specific glass compositions. , No particular trend was observed either with the composition changes or with different elements present in the systems, suggesting that the proposed MLP describes with comparable accuracy glasses within the full compositional range of glass formability. Albeit the virial was not included in the training, its prediction is accurate with MAE = 3.254 eV.…”
Section: Resultssupporting
confidence: 82%
“…Machine learning-based potentials (MLP) have attracted more and more attention in recent years as an alternative approach to simulate atomic interactions in glasses. They have been already applied in other fields such as battery materials, catalysis, and drug design . The basic idea is to first train the chosen ML algorithm using accurate ab initio data, typically from DFT, and then to reproduce the potential energy surface at a much lower computational cost, making larger systems and longer timescales accessible without losing accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the less amount of 3‐rings generated by the MLP‐MD simulations compared to the KMG model at low Na 2 O content is not due to the modeling procedures. A previously developed MLP for modeling lithium borate glasses 26 also underestimated boroxol rings in borate glass. One possible explanation for this is the significant challenge in obtaining borate glass models with an adequate number of boroxol rings using any molecular modeling technique, such as CMD and AIMD simulations, which hinders to obtain appropriate training data for constructing MLP.…”
Section: Resultsmentioning
confidence: 99%
“…The other challenge facing CMD simulations is the formation of the 3‐rings. Indeed, it has been demonstrated that the force fields reproduce few 3‐rings, even if boron atoms appropriately bind to oxygen atoms 18,26 . Takada et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation